Organizing Latin American workers in Japan: The case of the community union MIE as an alternative space of regulation. Issue 3 (3rd April 2017) - Stewart, Paul; Danford, Andy; Urano, Edson
Abstract : Purpose: The purpose of this paper is to assess difficulties facing the unionization of foreign workers focusing on the experience of trade unionists in Union MIE, an exemplar of what in Japan is known as a community union (sometimes described as a form of Minority union – Stewart, 2006). Union MIE is characterized by its orientation to the social and political agenda of Latin American workers, among whom Brazilians form the most numerous group. The paper also addresses the precarious nature of workers' employment including the condition of labor. The increasing significance of community unions raises the question as to the possibility of the reregulation of worker interests in ways not fully encompassed by traditional labor market-focused unions. Design/methodology/approach: The paper explores unique interviews using snowball technique and direct questionnaires to union membership of community union in Japan. Findings: The increasing significance of community unions raises the question as to the possibility of the reregulation of worker interests in ways not fully encompassed by traditional labor market-focused unions. In addition to having relevance to the wider discussion on union decline, this paper contributes to the debate on migrant workers, their condition of labor and one form of labor organization responsive to their concerns. Research limitations/implications: A comparative approach would add even more to the weight of evidence accrued in the paper. Practical implications: Mainstream trade unions need to anticipate that the concerns of migrant and precarious workers will become increasingly common among their erstwhile "regularly" employed membership and so the activities of community and minority unions need to be taken on board in an organic, as opposed to an opportunistic, manner. Originality/value: From unique interviews using snowball technique and direct questionnaires to union membership of community union in Japan, the paper presents original data not typically accessible in Anglo-Saxon research tradition.